Schugurensky, D. y Wolhuter, Ch. (2020). Global Citizenship Education and Teacher Education. Theoretical and practical issues. Nueva York y Oxon: Routledge, 298 páginas. - Castellví Mata, Jordi (2020)
Fil: Castellví Mata, Jordi. Universidad Internacional de La Rioja.